Ring band - pass filter (RBPF) for global positioning system (GPS) / Nazatul Fariza Abdul Halim - Abdul Halim, Nazatul Fariza (2009)
This work presents the design, simulation and analysis of a band-pass filter based on ring shape for microwave application. In designing the filter, Tschebycheff approach was used and simulation was carried out using commercial simulation software. The prototype filter was fabricated on the RT Duroid 4350B dielectric substrate (sr) with the value of 3.48. The operating frequency is from 1.559 to 1.610 GHz with the cut-off frequency at 1.584 GHz and bandwidth of 51 MHz. it is observed that there was a slight discrepancy between the measured frequency response of insertion loss and return loss compare to simulated frequency response.